Influence of leucine supplementation on serum amino acid concentration and anaerobic running performance - Mero, A. A.; Nummela, A. T.; Rusko, H. K.; Pontinen, P. J.; Oja, S. S. (Medicine & Science in Sports & Exercise, 1997)
The effects of leucine supplementation on serum amino acid concentrations and anaerobic running performance were assessed. Ss performed under placebo and leucine conditions. Leucine supplementation significantly increased the total concentration of branched-chain amino acids. Running velocity or peak lactate did not differ between the placebo and supplementation conditions. Leucine supplementation diminished the serum isoleucine and valine concentrations during anaerobic running but had no effect on performance. Implication. The ingestion of leucine as a way of stimulating the presence of branched-chain amino acids does produce that effect but does not alter anaerobic running performance.